Theoretical and methodological aspects of development management of enterprises of oil and gas industry - Фадєєва, І. І.; Савчин, Л. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Tools for managing business development rather significant, and further it will evolve and be enriched with new solutions. The article discusses approaches to the interpretation of the essence of definitions of "business management", "enterprise development" and "development company management", clarified their values and economic sense. The main instruments that influence the development of oil and gas companies are identified. Generalization and systematization of the problem field of management development companies considering international experience identifying and solving such problems are presented. The choice of theoretical, methodological and applied principles of management of the development of modern enterprise.